PENGEMBANGAN DESA WISATA SINDANGKASIH DAN DESA WISATA SITU CANGKUANG DI KABUPATEN GARUT MELALUI PENDEKATAN PENTA HELIX - Muhammad Reynaldi Aulia Rahmat; Evi Novianti; Yustikasari Yustikasari (LPSDI Bina Patria, 2023)
Today's tourist villages have become the choice of tourist destinations. By adding a more dynamic variety of destinations in a tourism area. Developments in tourist villages will have an impact on the economy of a village area, namely increasing the income of rural communities. Sindangkasih Tourism Village and Situ Cangkuang Tourism Village located in Garut Regency have similarities in tourism potential from natural, historical, cultural tourism, to artificial tourism that need to be developed. The pentahelix model (government, academics, business people, communities, and mass media) has their respective roles in the development of the two tourist villages. This research aims to discuss the role of pentahelix actors in the development of tourist villages. Through qualitative research methods with data collection techniques direct observation, interviews with informants, and documentation. The potential of the Sindangkasih and Situ Cangkuang Tourism Villages needs to be developed and the pentahelix actors have a role in the development of the two tourist villages, but cooperation between the actors needs to be improved.